Power and Responsibility in Chinese Foreign Policy - Yongjin Zhang, Greg Austin (ANU E Press, 2014)
Why does China behave as it does in its foreign policy? How and why does China behave differently from other Great Powers in international society? How does China's understanding of the responsibility associated with its rising power explain its international behaviour? In what sense can we argue that China has become more (or less) responsible in international relations? In China's search for its Great Power status, how do domestic politics and historical experience matter in its understanding of the responsibility of power? Does China think it is well served by a responsible approach to the rights and duties bestowed on it by international society? How do others evaluate whether China is living up to its obligations as a rising power? These are among a particular set of questions that individual essays published in this collection reflect on and debate. Collectively, this book explores a gap in the existing literature on the studies of Chinese foreign policy and focuses on whether and how a particular idea-the idea of the responsibility of power-helps to shape as well as explain China's changing behaviour in international relations. The rising power of China has been one important theme in the discourse of post Cold War international relations. Recent and current debates have revolved around two important questions.What are the implications of the rise of China for regional and global international order? And how should others, particularly the United States, respond to the rise of China? 1 On the first question, a realist reading suggests that changing power relations, particularly those of a rising power vis-a-vis the pre-eminent power (that is, China vis-a-vis the United States), will inevitably lead to conflicts and even war. Further, China is revisionist and destabilising because of its historical grievances and irredentist agenda. It is bent on challenging and changing the existing international order. A realist reading is quick to point out that, historically, the rise of Japan and Germany as two have-not powers has provoked major wars. Even a liberal reading of the rise of China is likely to reinforce the realist wisdom. China is the remaining Leninist state.